Zamzam Water Surpasses Global Standards in Quality and Mineral Content: Air Zamzam Melampaui Standar Global dalam Kualitas dan Kandungan Mineral - Abed Sultan Hassan; Nadia Abd Ellatif Ali (Academia Open, 2024)
This study investigates the physical, chemical, and bacteriological properties of Zamzam tap water and two popular bottled waters, "Rounaq" and "Naba' Al- Rayan," in Diyala Governorate. Conducted at Al-Rafidain University College and the Central Public Health Laboratory in Baghdad, the research analyzes taste, odor, color, pH, essential minerals, and bacterial contamination. Findings indicate that Zamzam water excels in sensory qualities and contains beneficial minerals like potassium and magnesium within safe limits, with no bacterial contamination detected. These results affirm Zamzam's superior quality and underline the necessity for regular quality checks of bottled waters to ensure public health safety. Highlights: Superior Sensory Qualities: Zamzam water was notably superior in taste, odor, and color compared to the other bottled waters tested. Mineral Content and Safety: All water samples contained essential minerals like potassium and magnesium within safe limits, confirming their nutritional value and compliance with health standards. Bacterial Purity: No bacterial or pathogenic contamination was detected in any of the water samples, ensuring their safety for consumption. Keywords: Zamzam Water, Bottled Water Quality, Mineral Content, Bacteriological Safety, Sensory Properties